The association between preoperative anemia and postoperative mortality among non-cardiac surgical patients in Northwest Ethiopia: a prospective cohort study - Misganew Terefe Molla; Amanuel Sisay Endeshaw; Gebrehiwot Asfaw; Fantahun Tarekegn Kumie (BMC Anesthesiology)
Abstract Introduction In a low-income country, the impact of preoperative anemia on postoperative mortality among noncardiac surgery patients is little understood. As a result, we aim to investigate the association between preoperative anemia and postoperative mortality in noncardiac surgery patients in Northwest Ethiopia. Methods This is a prospective follow-up study of 3506 noncardiac surgery patients who were included in the final analysis between June 1, 2019, and July 1, 2021. We used a propensity score-match analysis to group anemic and non-anemic patients. The propensity score match analysis took into account age, gender, comorbidities, American Society of Anesthesiologists physical status, urgency of surgery, and trauma. Patients with and without preoperative anemia were divided into a 1:1 ratio in a propensity score balance. The association between preoperative anemia and postoperative mortality was determined using adjusted odds ratios and 95% confidence interval. Results This study included 3506 noncardiac surgery patients, of which 1532 (43.7%) had preoperative anemia. The propensity score-matching results reveal that one-to-one nearest neighbour propensity score matching without replacement was successful for 1351 pairs of surgical patients. The postoperative 28-day mortality rate for anemic patients was 53 (3.9%), with (OR:1.63; 95% CI: 1.05–2.54). Conclusion The study found that patients undergoing noncardiac surgery in Northwest Ethiopia had a higher rate of preoperative anemia than those in high-income countries. Preoperative anemia had a significant association with 28-day mortality after surgery.